How can implementation intentions be used to modify gambling behavior? - St Quinton, Tom (Frontiers in Psychology, 2022)
Problem gambling can cause significant harm, yet gambling rates continue to increase. Many have the motivation to stop gambling but are unable to transfer their positive intention into successful behavior change. Implementation intentions is an effective strategy in bridging the gap between intention and many health behaviors. However, despite its popularity in health psychology, the strategy has rarely been used in gambling research. This mini review demonstrates how implementation intentions can be used to modify gambling behavior. Adopting the strategy could help reduce the number of people with gambling problems.